PENDAMPINGAN MASYARAKAT DALAM PELESTARIAN BUDAYA ROKAT DI DESA CONDONG - Herwati, Herwati; Qomariyah, Munawarotul; Aziziyah, Aziziyah; Izza, Nur Laily Alfiatul; Asyanti, Asyanti (Kalam Nusantara Institute, 2024)
Culture is the way of life shared by a group of people, including the values, norms, language, beliefs, and practices that shape their identity. Condong Village is a village that has sloping land, that's why the village is called Condong Village. Condong Village has several assets, including: personal assets, social assets, spiritual assets, institutional assets, natural assets and physical assets. This mentoring activity aims to preserve and develop the almost extinct rokat tradition by providing assistance to community leaders in the village of Pikan. The aim of this Rokat is to implement research results through community service in the form of empowerment. The research method used is the Asset Based Community Development (ABCD) approach by developing spiritual assets owned by the community, one of which is the preservation of rock culture. The stages used in this stage are preparation, implementation, evaluation. The results obtained from the mentoring were found to be the culture of bridal rokat being carried out when there are 3 siblings, 1 boy and 2 girls or 2 boys and one girl. The bridal ceremony is performed at midnight right in front of the bride's house. First, it starts with the reading of old book discourses by the person in charge of leading the rokat, which is then followed by a shower by the rokat leader, then parents and close family members. As for the data or tradition of Rokatan, it is becoming increasingly known to the village community, especially after providing assistance by means of socialization by community leaders to members of the community at religious events.